Paleo sea-level changes and relative sea-level indicators: Precise measurements, indicative meaning and glacial isostatic adjustment perspectives from Mallorca (Western Mediterranean) - Lorscheid, Thomas; Stocchi, Paolo; Casella, Elisa; Gómez-Pujol, Lluis; Vacchi, Matteo; Mann, Thomas; Rovere, Alessio (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
Paleo relative sea-level (RSL) indicators formed during the Marine Isotope Stage (MIS) 5e have been reported by a large number of studies worldwide. Despite this, three main aspects are seldom reported: (1) use of high-precision survey techniques applied to MIS 5e RSL indicators; (2) application of modern analogs to understand the indicative meaning of MIS 5e RSL indicators; (3) estimates of the effects of glacial isostatic adjustment (GIA) on the MIS 5e records. In this study, we show how the three points above have been addressed in a focused study on Last Interglacial outcrops on the island of Mallorca. We measured the elevation of several RSL indicators with high-accuracy differential GPS (vertical accuracies down to 0.1 m) and we established the relationship between each RSL indicator and the paleo sea level through calculation of the indicative meaning for each RSL indicator. In particular, we present a novel technique to calculate the indicative meaning of fossil beach deposits with a phase-averaged morphodynamic model (CSHORE). We show how this approach helps overcoming difficulties with the survey of the modern analogs for these indicators. Our results show that two paleo RSLs are imprinted in Mallorca at + 2.9 ± 0.8 m and + 11.3 ± 1.0 m. We then compare our field-based results with modelled paleo RSL, calculated from the predictions of the ice-earth coupled ANICE-SELEN model, using few different ice-sheet melting scenarios during MIS 5e. We conclude that indicative ranges can be derived from relatively simple morphodynamic models and that the comparison of field-derived and modelled RSL values is a good method to validate possible scenarios of MIS 5e sea-level variability, especially in absence of precise dating.